Analisis Pengaruh Peran Intelijen TNI AL Dalam Mendukung Keamanan Laut di Selat Malaka - Catur Hendrawan (Jurnal Multidisiplin Indonesia, 2024)
The Strait of Malacca is a vital maritime route connecting the Indian Ocean and the South China Sea, becoming an important global trade artery but also vulnerable to various security threats such as human trafficking, drugs and maritime piracy. In this context, the Indonesian Navy's intelligence role has a crucial role in gathering information, analyzing and responding to potential threats to maintain regional security. This research aims to evaluate the role of Indonesian Navy intelligence in supporting maritime security in the Malacca Strait, with a focus on information collection strategies, the technology used, and international cooperation through the Malacca Straits Patrol (MSP). The main objective is to identify the effectiveness of intelligence strategies in overcoming complex security challenges in the Malacca Strait. The research uses a qualitative approach with case studies as the main method. Primary data was obtained through interviews with high-ranking Indonesian Navy officials and intelligence personnel who were directly involved in the Malacca Strait, as well as direct observation of maritime activities. Secondary data includes official documents, previous research reports, and other relevant sources of information. The research results show that Indonesian Navy intelligence is effective in gathering information through advanced technology such as radar systems and air surveillance to monitor ship activities. Cooperation with neighboring countries through MSP also improves information exchange and operational coordination, strengthening joint presence in dealing with cross-border threats. However, challenges faced include a lack of technological resources and cross-agency coordination that affect the effectiveness of maritime surveillance.